Access, autonomy, and affordability: ethical and human rights issues surrounding multigene panel testing for cancer in Japan and Switzerland - Nakasato, Kate; Manz, Carlotta; Kato, Kazuto (Frontiers in Genetics, 2024)
Advancements in precision medicine and genomics have led to prospects in a wide range of clinical fields, including oncology. In particular, developments in next-generation sequencing (NGS) multigene panel tests have led to the possibility of tailoring treatment to the specific genomic markers of a patient’s cancer. However, findings from current literature suggest that the path to implementation and uptake of genomic medicine is not without uncertainties and challenges. To better understand the current challenges to the implementation of genomic medicine services, we investigated the current state of patient access to genomic medicine in Japan and Switzerland. In this investigation, we focused on equal access, patient autonomy, and healthcare affordability. Results have shown that although multigene panel testing is in principle covered by health insurance in both countries, barriers exist in terms of where the tests are available, comprehensive information for patients, and the affordability of not only the test itself but the overall process from diagnosis to treatment. These results suggest a need to continue examining a more diverse range of clinical landscapes for genomic medicine to reveal more nuanced understandings of barriers to implementation and thus better identify best practices for overcoming them.